A Small Country with Big Ambitions: Does This Include the Gifted? - Margaret Sutherland; Catherine Reid (Education Sciences, 2023)
Scotland is a small country with an education system whose roots lie within an inclusive and egalitarian approach to the education of young people. Subsequent legislation, policies, and curriculum frameworks have been influenced by this, and also by the international move toward equitable, inclusive, and quality lifelong learning for all. Supporting those who are highly able/gifted and talented against such a backdrop offers both opportunities and challenges. In this qualitative study, the Global Principles for Professional Learning in Gifted Education are used to interrogate recent key legislation; the current curriculum framework, Curriculum for Excellence, and the National Framework for Inclusion; to ascertain the extent to which this inclusive approach, on paper, affords in-class and school-based support for gifted and talented/highly able learners. The results indicate that the legislative and policy frameworks coalesce with the Global Principles. While legislation does not change practice, it does influence and shape practice, and so can be used as a springboard for developing dynamic, culturally appropriate opportunities for Scotland’s gifted young people.